2013
DOI: 10.1111/boj.12009
|View full text |Cite
|
Sign up to set email alerts
|

Four o'clock pollination biology: nectaries, nectar and flower visitors in Nyctaginaceae from southern South America

Abstract: Floral nectary structure and nectar sugar composition were investigated in relation to other floral traits and flower visitors in contrasting species of Nyctaginaceae from southern South America, representing four tribes (Bougainvilleeae, Colignonieae, Nyctagineae, Pisoneae). Our comparative data will aid in the understanding of plant–pollinator interactions and in the development of hypotheses on the origin of floral and reproductive characters in this family. The nectaries are located on the inner side of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…In general, those same groups of floral visitors have been recorded previously for the annual species studied or other species belonging to the same plant families (Zimmerman 1977;Adams et al 1981;Townsend 1993;OsorioBeristain et al 1997;Nores et al 2013;Bizecki 2014;Moore 2014). In addition, we found that abundance, diversity, and composition of the community of floral visitors of annual plants vary through space.…”
Section: Discussionsupporting
confidence: 78%
“…In general, those same groups of floral visitors have been recorded previously for the annual species studied or other species belonging to the same plant families (Zimmerman 1977;Adams et al 1981;Townsend 1993;OsorioBeristain et al 1997;Nores et al 2013;Bizecki 2014;Moore 2014). In addition, we found that abundance, diversity, and composition of the community of floral visitors of annual plants vary through space.…”
Section: Discussionsupporting
confidence: 78%
“…The 3–9 stamens (1–3 in Boerhavia diffusa ) are connate at the base, forming a staminal tube (Nores et al, 2013). Filaments are mostly unequal and exserted.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies will explore the relationships between these models and pollen traits (López et al, 2006) and/or compatibility systems (López and Galetto, 2002; Nores et al, 2013). Allionia , Boerhavia , and Mirabilis produce relatively few large, starchy pollen grains, compared with many small lipidic grains in Bougainvillea (López et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, plant–pollinator interaction has been the focus of much discussion and debate (Fenster, Armbruster, Willson, Dudash, & Thomson, ; Gómez, Abdelaziz, Lorite, Munõz‐Pajares, & Perfectti, ). Plant species that depend on animal pollinators for their reproduction have developed many different phenotypes traits, such as floral display, flower architecture and nectar (Arias‐Cóyotl, Stoner, & Casas, ; Nores, López, Rudall, Anton, & Galetto, ). Insect mediated pollination, the transfer of pollen within or between flowers via insect vectors, is one such ecosystem service that benefits human populations and agriculture (Fisher, Turner, & Morling, ).…”
Section: Introductionmentioning
confidence: 99%